Development of Delay Models for Roundabouts - G. Sofia, Gandhi; H. Al-Haddad, Abdulhaq; Saeed Al-Haydari, Israa (Journal of Engineering and Sustainable Development, 2012)
The purpose of this research is to develop an empirical model for total delay time prediction at roundabouts as a function of influence traffic and geometric features. Four roundabouts of fifteen approaches with different characteristics are selected in Karbala City. The traffic parameters are measured using a video recording technique. Geometric elements are measured through field surveys and satellite images. A statistical approach is used to develop three delay models (linear regression models with 95% and 50% confidence levels, and polynomial regression models with 95% confidence levels). The statistical analysis indicates that both geometric and traffic variables have a significant effect on the delay time. The entry radius and circulating traffic have the greatest influence. These models have been compared with the SIDRA delay model. It is found that although SIDRA delay overestimates delay time at a high delay range, it does not have a significant difference with the field delay at 95% confidence level.